The Role and Position of The Philosophy of Mathematics in Mathematics Learning in The Merdeka Curriculum According to Paul Ernest’s Concept of "The Philosophy of Mathematics” - Angeline, Rachel (Jurnal Indonesia Sosial Sains, 2025)
The Philosophy of Mathematics holds a significant yet underexplored role in shaping mathematics education, particularly within Indonesia’s Merdeka Curriculum. Rooted in the principles of autonomy, critical thinking, and creativity, the curriculum provides a framework for integrating philosophical perspectives to enhance student engagement and understanding. This study critically examines the application of Paul Ernest’s social constructivist philosophy in mathematics learning, focusing on its theoretical implications and practical integration in classroom practices. Using a qualitative critical review approach, this research analyzes curriculum guidelines, academic literature, and empirical studies. The thematic analysis highlights the alignment between the Merdeka Curriculum’s principles and Ernest’s emphasis on collaborative learning and contextualized problem-solving. Interviews with educators reveal both challenges and opportunities in fostering a philosophical mindset, such as the need for teacher training and the potential for deeper conceptual understanding through reflective learning. The findings demonstrate that integrating the Philosophy of Mathematics enriches the teaching process by promoting critical thinking and connecting mathematical concepts to real-world applications. However, challenges such as limited teacher preparedness and systemic constraints need to be addressed. This study concludes by emphasizing the transformative potential of philosophy in mathematics education, advocating for a more intentional incorporation of philosophical principles to prepare reflective and competent learners.